DOOR TO DOOR ENGLISH TEACHING IN TAKA BONERATE ISLAND DURING PANDEMIC SITUATION AT SMAN 5 SELAYAR - Bungsuwati; Hasnawati Latief; Farisha Andi Baso (English Language Teaching Methodology, 2022)
This research aims to find out the effectiveness of Door-to-Door method and also the obstacles faced by the English teacher at SMAN 5 Selayar that used Door to Door method. The study used Descriptive Qualitative methods and collect data through collect result study of students, in-depth interview and audio record. The sample of this study was result study of students from 2 classes and English teachers at SMAN 5 Selayar who was use the Door to Door method. Samples was taken by using purposive techniques. Analysis data uses reduction data, display data and conclusion. Based on the findings of the study, there are 2 results obtained the first effectiveness of the use of Door to Door which can be seen from the results study of students, for class XIIS 1 all of a total of 18 students they get a score above 75 (KKM), For class XIIS 2, 13 people out of 16 total students get a score above 75 (KKM). For obstacles there are three, namely transportation costs, time and energy. After using the Door to Door method, students' learning outcomes increased and 75% of each class met the score of 75 (KKM) and it proved that this method was effectively used during the pandemic, and there were several obstacles faced by English teachers in the implementation of the Door to Door method, namely greater transportation costs, longer time taken and greater family energy. Therefore, based on the results, it is recommended to use the Door to Door method during the pandemic, especially at the remote area.